2019
DOI: 10.32604/cmc.2019.03760
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Three-Factor User Authentication Protocol for the Information Perception of IoT

Abstract: With the development of computer hardware technology and network technology, the Internet of Things as the extension and expansion of traditional computing network has played an increasingly important role in all professions and trades and has had a tremendous impact on people lifestyle. The information perception of the Internet of Things plays a key role as a link between the computer world and the real world. However, there are potential security threats in the Perceptual Layer Network applied for informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Thus, Attribute-Based Communication Control (ABCC) [108] has been introduced. A novel lightweight authentication protocol [109] has been proposed to protect password, which is based on smart card and biometric identification. Moreover, for multi-cloud interaction and collaboration across several connected communities, there needs distributed computing enabled by dynamic trust frameworks.…”
Section: Open Challenges and Future Directionsmentioning
confidence: 99%
“…Thus, Attribute-Based Communication Control (ABCC) [108] has been introduced. A novel lightweight authentication protocol [109] has been proposed to protect password, which is based on smart card and biometric identification. Moreover, for multi-cloud interaction and collaboration across several connected communities, there needs distributed computing enabled by dynamic trust frameworks.…”
Section: Open Challenges and Future Directionsmentioning
confidence: 99%
“…In fact, policies and credentials are revealed only when they are required, avoiding the disclosure of extra information when it is not needed. This is an important aspect to take into consideration in order to develop authentication processes for the IoT field [35]. Finally, regarding the evaluation models, Moyano identified that a trust level is always present and it could be uni-dimensional or multi-dimensional.…”
Section: Related Workmentioning
confidence: 99%
“…Context-aware security can take into account the growing and different threats within IoT. For example, instead of static three-factor authentication as proposed in [5], the Context Adaptive Authentication Service (CAAS) allows a user to dynamically choose a type of authentication: simple (one-factor) or strong (two-factor or three-factor). e chosen authentication method depends on the risk associated to the user's context [6].…”
Section: Introductionmentioning
confidence: 99%